Does high PD-L1 expression reduce the risk of relapse after definitive surgery in patients with oral cavity cancer? - Babayev, Parvin; Ismayilov, Rashad; Kuscu, Oguz; Akyildiz, Arif; Kurtulan, Olcay; Pamuk, Erim; Guler Tezel, Yesim Gaye; Gullu, Ibrahim Halil (Acta Oto-Laryngologica, 2025)
Background: Uncovering the molecular mechanisms of cancer pathogenesis is crucial for improving survival outcomes. Aims: This study investigates the impact of programmed death ligand 1 (PD-L1) expression on the risk of progression in patients with oral squamous cell carcinoma (OSCC). Materials and methods: The retrospective study included adult patients diagnosed with OSCC between January 2012 and December 2023. PD-L1 expression in tissue removed by definitive surgery was evaluated using immunohistochemistry, and tumor proportion score (TPS) and combined positive score (CPS) were calculated. Survival analyses were performed to assess its prognostic implications. Results: Among the 96 patients, TPS and CPS were 20% or above in 52 (54.2%) and 65 (67.7%) cases, respectively. TPS ≥20% was associated with mucosal lip location, earlier disease stage, and decreased risk of progression. The multivariate Cox regression model revealed that stage III/IV disease (HR: 2.176, 95%CI: 1.085–4.376, p =.029) and TPS ≥20% (HR: 0.241, 95%CI: 0.066–0.879, p =.031) were independent risk factors for progression-free survival. Conclusions: The study revealed that increased tumoral PD-L1 expression may reduce the risk of progression in patients with OSCC. Significance: These findings underscore the potential prognostic significance of PD-L1 expression in OSCC following surgical resection.